Features of electrode wear during EDM of mild steel with TaC-Cu powder compacted electrodes - Khan, Ahsan Ali; Nazi Nadin, Mohd Faiz; Mohd Hambiyah, Mohammad Azhadi (International Islamic University Malaysia, 2011)
Abstract. Features of tantalum carbide-copper powder compacted electrodes during EDM of mild steel have been studied. It was found that during EDM electrode wear increases with increase in current and spark on-time. Electrode wear is inversely proportional to spark off-time. Due to increase in off-time, energy density decreases that caused reduction of electrode wear. Interaction effects show that the influence of current and off-time is almost equal. However, interaction effect of spark on-time and off-time is significant.